Jung, the Tao, and the Classic of Change - Karcher, Stephen (Journal of religion and health, 1999)
This paper developed from a series of lectures and seminars given in London and Cambridge, England, in early 1999 and takes into consideration participants' comments. In it, Dr. Karcher looks at the connection between Jung's psychology and the Chinese oracle book called I ChingorYijing,usually translated as Classic of Change.This connection centers on a mysterious symbolic awareness that Chinese philosophers call tao or way. This symbolic awareness involved both Jung and his psychology in a very special "orientation," a Journey to the East.